An Argument on The Narration of Children’s Story “Kupu-Kupu yang Tidak Mau Tidur” By Clara Ng - Andalusia Neneng Permatasari (Metalingua: Jurnal Penelitian Bahasa, 2017)
This research discusses argument in narrative text which is “Kupu-Kupu yang Tidak Mau Tidur” by Clara Ng. The result of this research shows that narrative elements found in this children story are abstraction, orientation, evaluation, complication, result, and coda. Most part of those narrative elements are constructed by logic interprepositions relation, which are reason-RESULT relation, consession-CONTRAEXPECTATION, and grand-CONCLUSION. Those relations are logic relations which show argument that the author wants to convey in the story. Narrative elements which contain argument are evaluation, complication, and result. Therefore, the narrative texts not only tell about events but also convey arguments.